Religious Narratives And Networked Learning Spaces: Using Blogs To Connect Individuals To History - Williamson, George S.; Dennen, Vanessa (AoIR Selected Papers of Internet Research, 2017)
This case study examines student use of semi-private, “disposable blogs” in a History of Religion course, focusing on whether (a) the blogs helped students explore personal connections to readings and the course materials (b) the semi-private nature of the blogs negated the learning benefits of using blogs (c) the blogs supported student learning processes. Students were expected to write two blog posts per week, once in response to a prompt and once on a course-related topic of their choosing. Findings show that students were favorably disposed to writing about course content in a blog format and that the restricted audience of semi-private blog space did not hinder their desire to communicate. Students were particularly interested both in having their instructor leave comments to affirm or challenge their thinking, and in reading blog posts written by their instructor. Although students were positively disposed toward blogging, finding time to blog regularly was nonetheless a challenge for many students. Student blog grades were positively correlated to their final exam grades. Collectively, the findings suggest that the space and format in which students write is important, and that networked spaces can be useful for supporting student learning even when audience is restricted.